IMPLEMENTASI PROGRAM DUNIA INDUSTRI, DUNIA USAHA DAN DUNIA KERJA DI SEKOLAH - Kiki Eva Maria (UNIB Press, 2022)
This study aims to find out how to plan, organize, implement and evaluate the cooperation program with DUDIKA, especially the Field Work Practice program. The method used is descriptive qualitative with data collection methods, interview observations and documentation. The research subjects were the Principal, Deputy Principal for Curriculum, Deputy Principal for Quality Assurance, Vocational Maple Teachers, and one of DUDIKA is PT. POS Pagar Alam City . Data analysis is to perform data reduction, data presentation and conclusions and verification. The results of the research that has been done at SMK Muhammadiyah and PT. POS Kota Pagar Alam has several research findings, such as (1) Planning of industrial work practice activities for DUDIKA is based on synchronizing joint curriculum, making MoU between schools and DUDIKA, student readiness planning (competency mapping), and placement planning (DUDIKA place mapping). in accordance with the competence of students required by DUDIKA. (2) Organizing the industrial work practice activity program by dividing the organizational structure and division of labor, as well as placing students in each DUDIKA. (3) The implementation of the industrial work practice program for DUDIKA is carried out flexibly in accordance with the policies of each school. By conducting training, direct industrial work practices, as well as recruiting students who meet DUDIKA's needs. (4) Evaluation of the industrial work practice program for DUDIKA is carried out with an assessment from DUDIKA using an assessment format from each school